Phenotypic Spectrum and Prognosis of Epilepsy Patients With GABRG2 Variants - Yang, Ying; Niu, Xueyang; Cheng, Miaomiao; Zeng, Qi; Deng, Jie; Tian, Xiaojuan; Wang, Yi; Yu, Jing; Shi, Wenli; Wu, Wenjuan; Ma, Jiehui; Li, Yufen; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective: This study aimed to obtain a comprehensive understanding of the genetic and phenotypic aspects of GABRG2-related epilepsy and its prognosis and to explore the potential prospects for personalized medicine. Methods: Through a multicenter collaboration in China, we analyzed the genotype-phenotype correlation and antiseizure medication (ASM) of patients with GABRG2-related epilepsy. The three-dimensional protein structure of the GABRG2 variant was modeled to predict the effect of GABRG2 missense variants using PyMOL 2.3 software. Results: In 35 patients with GABRG2 variants, 22 variants were de novo, and 18 variants were novel. The seizure onset age was ranged from 2 days after birth to 34 months (median age: 9 months). The seizure onset age was less than one year old in 22 patients (22/35, 62.9%). Seizure types included focal seizures (68.6%), generalized tonic-clonic seizures (60%), myoclonic seizures (14.3%), and absence seizures (11.4%). Other clinical features included fever-sensitive seizures (91.4%), cluster seizures (57.1%), and developmental delay (45.7%). Neuroimaging was abnormal in 2 patients, including dysplasia of the frontotemporal cortex and delayed myelination of white matter. Twelve patients were diagnosed with febrile seizures plus, eleven with epilepsy and developmental delay, two with Dravet syndrome, two with developmental and epileptic encephalopathy, two with focal epilepsy, two with febrile seizures, and four with unclassified epilepsy. The proportions of patients with missense variants in the extracellular region and the transmembrane region exhibiting developmental delay were 40% and 63.2%, respectively. The last follow-up age ranged from 11 months to 17 years. Seizures were controlled in 71.4% of patients, and 92% of their seizures were controlled by valproate and/or levetiracetam. Conclusions: The clinical features of GABRG2-related epilepsy included seizure onset, usually in infancy, and seizures were fever-sensitive. More than half of the patients had cluster seizures. Phenotypes of GABRG2-related epilepsy were ranged from mild febrile seizures to severe epileptic encephalopathies. Most patients with GABRG2 variants who experienced seizures had a good prognosis. Valproate and levetiracetam were effective treatments for most patients.